Evidence for a non-canonical role of HDAC5 in regulation of the cardiac Ncx1 and Bnp genes - Harris, Lillianne G. (Nucleic Acids Res, 2016)
Class IIa histone deacetylases (HDACs) are very important for tissue specific gene regulation in development and pathology. Because class IIa HDAC catalytic activity is low, their exact molecular roles have not been fully elucidated. Studies have suggested that class IIa HDACs may serve as a scaffold to recruit the catalytically active class I HDAC complexes to their substrate. Here we directly address whether the class IIa HDAC, HDAC5 may function as a scaffold to recruit co-repressor complexes to promoters. We examined two well-characterized cardiac promoters, the sodium calcium exchanger (Ncx1) and the brain natriuretic peptide (Bnp) whose hypertrophic upregulation is mediated by both class I and IIa HDACs. Selective inhibition of class IIa HDACs did not prevent adrenergic stimulated Ncx1 upregulation, however HDAC5 knockout prevented pressure overload induced Ncx1 upregulation. Using the HDAC5((-/-)) mouse we show that HDAC5 is required for the interaction of the HDAC1/2/Sin3a co-repressor complexes with the Nkx2.5 and YY1 transcription factors and critical for recruitment of the HDAC1/Sin3a co-repressor complex to either the Ncx1 or Bnp promoter. Our novel findings support a non-canonical role of class IIa HDACs in the scaffolding of transcriptional regulatory complexes, which may be relevant for therapeutic intervention for pathologies.